Internalisasi Nilai-Nilai Akhlak dalam Upaya Menangkal Radikalisme di Madrasah Aliyah Hidayatul Faizien Garut - Ating Rukmana (JIECO: Journal of Islamic Education Counseling, 2021)
ABSTRACT The background of this research was the students’ moral crisis started from the assumption of the previous research in several Madrasah Aliyah in Garut showed that moral values have not been optimally internalized. It was because planning, implementing and evaluating have not been optimal, so it cannot prevented radicalism. The reason of this research was to obtained an overview about the planning, implementing, evaluating, problem, and solution about moral values in order to prevented radicalism in Madrasah Aliyah Hidayatul Faizien in Garut. The teological foundation was QS. An Nahl 90. The philosophical foundation used contructivism philosophy, theoritical basis discussed moral values, management and radicalism theori. This research used qualitative approach and data collection were carried out through triangual observation, interview and study documentation, while the data sources were principals, teachers and students. The result of this research showed: First, in planning aspect, internalization moral values in Madrasah Aliyah, the curriculum development in Madrasah compiled the curriculum structure, implemented curriculum, local content, extracurricular, habituation program, learning at boarding Madrasah, and evaluation. Second, in implementation aspect, the teachers applied several method, there were uswah/exemplary method, habituation method, advice method, pay attention mathod, and also reward and punishment method. Whereas the values instilled to the students divided into two values, there were ilahiyah values included belief and islam, taqwa, soul, tawakal and grateful. Insaniyah values included integrity, discipline, piece, responsibilty, tolerance and love country. Third, evaluation aspect divided into two kinds of evaluations, there were learning result evaluation and learning process evaluation. The assessment (Evaluation) internalization of moral values in Madrasah Aliyah in Garut used various forms and techniques, mastery learning and continuity evaluation. Fourth, the problems of internalization of moral values were internal factor (students) and eksternal factor (surroundings). Fifth, the solutions were teacher teaches islam contextually, instilled the tolerance values, piece, and be able to appreciate every differences, gained a good cooperation with parents and society. The conclusion of this research was the implementation process used continuity habituation, exemplary, adviced mothod/motivation, and superintendent as a main method in the internalization of moral values to prevented radicalism process with recovered management.